Free listening - Waltham-Smith, Naomi 1983- (University of Nebraska Press, 2024)
Free Listening argues that, instead of free speech, progressives should claim the more radical mantle of free listening and abolish obstacles to equality of audibility
Keywords: Freedom of expression-United States; Zuhören; Meinungsfreiheit; Progressismus; USA